A survey to determine self-reported confidence amongst emergency centre nurses in initiating bls across emergency centres in Cape Town - Maharaj, Suvarna (Stellenbosch : Stellenbosch University, 2017)
Thesis (MMed)--Stellenbosch University, 2013.